Development of HPTLC Fingerprinting for Different Extract of G. Asiatica Linn. Leaf and Fruit. (International Journal of Scientific Research and Management (IJSRM), 2019)
HPTLC Chromatogram of G. asiatica Linn. leaf, petroleum ether, chloroform, ethanol and aqueous extract, had shown the presence of 9, 5, 6 and 3 numbers of compounds respectively. There may be two compounds in all the extracts having similar Rf value 0.19 - 0.22 and Rf value 0.34 - 039. While HPTLC Chromatogram of G. asiatica Linn. fruits, petroleum ether, chloroform, ethanol, methanol and aqueous extract, had shown the presence of 11, 11, 10, 6 and 7 numbers of compounds respectively. There may be two compounds in all the extracts having similar Rf value 0.36 - 0.38 and Rf value 0.85 - 0.87.